Program Ekstrakulikuler Permainan Tradisional (Congklak) untuk Menumbuhkan Keterampilan Sosial Pada Siswa SMA dengan Autism Spectrum Disorder di Sekolah Khusus Pelita Bunda Samarinda - Maria Della Fajar Bulan; Mutia Mawardah (Indonesia Berdaya, 2023)
High school students are individuals who are completing formal education before finally graduating and continuing to college. High school students experience the transition from late adolescence to early adulthood. The age limit for high school students is between 15 to 18 years old. Puberty begins at the age of 10 and ends between the ages of 18 and 22. Social skills are one of the life skills that must be possessed by every individual, both regular and individuals with disabilities such as autism spectrum disorder. High school students with Autism Spectrum Disorder at Pelita Bunda Special School have social skills that tend to be low. Based on the existing problems, this community service was carried out to see the effect of the extracurricular program of the traditional game of congklak to foster social skills in high school students with Autism Spectrum Disorder. This type of research is development research (research and development) ADDIE model. ADDIE consists of 5 parts, namely : Analyze, Design, Development, Implementation, and Evaluation. The research data collection method uses: Observation (checklist technique), Interview and Documentation. Data analysis in this development research uses a Single Subject Research design experimental approach AbstrakSiswa sekolah menengah atas merupakan individu yang sedang menyelesaikan pendidikan formal sebelum akhirnya lulus dan melanjutkan ke perguruan tinggi. Siswa sekolah menengah atas mengalami transisi dari remaja akhir ke dewasa awal. Batas usia untuk siswa sekolah menengah adalah antara 15 sampai 18 tahun. Pubertas dimulai pada usia 10 tahun dan berakhir antara usia 18 sampai 22 tahun. Keterampilan sosial merupakan salah satu kecakapan hidup yang harus dimiliki oleh setiap individu baik yang regular maupun individu penyandang disabilitas seperti autism spectrum disorder. Siswa SMA dengan autism spectrum disorder di Sekolah khusus pelita bunda memiliki keterampilan sosial yang cenderung rendah. Berdasarkan permasalahan yang ada, pengabdian masyarakat ini dilakukan untuk melihat pengaruh dari program ekstrakulikuler permainan tradisonal congklak untuk menumbuhkan keterampilan sosial pada siswa SMA dengan autism spectrum disorder. Jenis penelitian ini adalah penelitian pengembangan (research and development) model ADDIE. ADDIE terdiri dari 5 bagian yaitu : Analyze, Design, Development, Implementation, dan Evaluation. Metode pengumpulan data penelitian menggunakan : Observasi (teknik ceklis), Wawancara dan Dokumentasi. Analisis data dalam penelitian pengembangan ini menggunakan pendekatan eksperimen desain Single Subject Research.